Life cycle and in vitro sporulation dynamics of Corinectria constricta, the causal agent of Pinus radiata stem canker, in Chile - González, Cristian D. (2020)
In 2008, a canker disease caused by the fungus Corinectria constricta was detected in southern Chile. The causal agent was previously identified as Neonectria fuckeliana (now Corinectria fuckeliana), which has been associated with stem cankers in Pinus radiata plantations in New Zealand since the 1990s. Many basic aspects of the life cycle of C. constricta remain unknown. The current study aimed to (a) document the periods during which C. constricta fruiting bodies are present in P. radiata plantations and associated factors; (b) determine the C. constricta life cycle in P. radiata plantations in southern Chile; and (c) evaluate, under in vitro conditions, the sporulation dynamics of ascospores. The first and second aims were carried out by evaluating affected plantations every 15 days, identifying asexual and sexual fungal structures, and recording the time periods when the structures were present. The third aim was achieved with in vitro tests in Petri dishes simulating humidity chambers. The life cycle was characterized by the presence of sporodochia from the Cylindrocarpon‐like (asexual form of C. constricta) morph during the autumn of 2012 (March–May). Subsequently, perithecia began to form on the sporodochia during April of 2012, taking approximately 3 months to mature (May–July), persisting for the rest of the year and providing inoculum to infect new trees. The development of perithecia in winter demonstrates that this is the most important period for dispersal and infection. In terms of sporulation dynamics, perithecia can release ascospores up to eight days following a wetting event; without this event, the spores are not released.